Sustainable Olympics - Ragan, Kristine Steffi; Brůna, Karel, 1973-; Gevorgyan, Kristine; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
It seems that the interest in hosting Olympic Games has declined in the last decade, mainly because of the reason that it costs too much in comparison with the gains generated for the host cities. Even the International Olympic Committee seems to be aware of this issue and has recently launched a concept with certain recommendations called the Olympic Agenda 2020. A brief history of the Olympics will be given, followed by relevant Olympic and financial definitions. In this thesis, the key analysis will be focused on the development of the most important characteristics of the Olympic Games, such as the NOCs, athletes and events. The main goal is to understand these developments and how they affect the economy of the Olympic Games. Furthermore, the situation today will be presented and compared with the recommendations suggested by the IOC, relevant for this thesis. Lastly, I will discuss my observations and present a vision for the future and for a sustainable direction of the Olympic Games.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses